Enhancing active transport demand Modelling by incorporating accessibility measures. (August 2018) - Saghapour, Tayebeh; Moridpour, Sara; Thompson, Russell G.
Abstract: Accessibility measures have been recognized as valuable input for decision support tools for land-use and transport planning. However, despite the relatively large number of available measures outlined in the literature, they are not widely used in planning practice, particularly in non-motorized transport modelling. Furthermore, the concept of availability of activities within acceptable walking/cycling travel distances may potentially affect the travel behaviour of pedestrians and cyclists, as distance has always been a significant barrier for travellers using active transport. Hence, this study aims to investigate the benefits of incorporating accessibility in active transportation modelling. For this purpose, three non-motorized accessibility measures are used in cluster analyses for classifying levels of access. Subsequently, three separate negative binomial regression (NBR) models are applied to examine the impact of including the access measure versus land-use measures in the models. Key findings indicate that the performance of active transport demand models is enhanced by incorporating accessibility as an explanatory variable as well as land-use measures. Highlights: This study aims to investigate the benefits of inclusion of accessibility measure in active transportation modelling. Regression models are applied to examine the importance of including accessibility measure in transport modelling. Findings indicate that the performance of active transport demand models is enhanced by incorporating accessibility measure.